(untitled) (Socio-economic relations in the digital society, 2019)
Brought development over of bank sector of economy to the origin of problems of high quality exact analysis of results of their activity. On the basis of structure of commercial banks and informative maintenance of statements of these organizations the methods of analysis and selection of information get out or developed with the minimum risk of losses. All these advantages are basis of the intellectual system with the use of methods of artifi cial intelligence.